2015
DOI: 10.1016/j.celrep.2015.09.063
|View full text |Cite
|
Sign up to set email alerts
|

FOXC1 Activates Smoothened-Independent Hedgehog Signaling in Basal-like Breast Cancer

Abstract: Summary The mesoderm- and epithelial-mesenchymal transition-associated transcription factor FOXC1 is specifically overexpressed in basal-like breast cancer (BLBC), but its biochemical function is not understood. Here we demonstrate that FOXC1 controls cancer stem cell (CSC) properties enriched in BLBC cells via activation of Smoothened (SMO)-independent Hedgehog (Hh) signaling. This non-canonical activation of Hh is specifically mediated by Gli2. We further show that the N-terminal domain of FOXC1 (aa 1–68) bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
133
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 49 publications
5
133
0
Order By: Relevance
“…FOXC1 can elicit Hh signaling in 2 BLBC cell lines MDA-MB-231 and HCC1500, neither of which expresses SMO. 6 Furthermore, the FOXC1 effect was not affected by SMO knockdown in SMO-expressing BLBC cells. 6 Consistent with our results, it has been shown that Hh signaling is highly active in breast CSCs that are characterized by the cell-surface glycoprotein CD44 C /CD24 ¡ phenotype.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…FOXC1 can elicit Hh signaling in 2 BLBC cell lines MDA-MB-231 and HCC1500, neither of which expresses SMO. 6 Furthermore, the FOXC1 effect was not affected by SMO knockdown in SMO-expressing BLBC cells. 6 Consistent with our results, it has been shown that Hh signaling is highly active in breast CSCs that are characterized by the cell-surface glycoprotein CD44 C /CD24 ¡ phenotype.…”
mentioning
confidence: 93%
“…6 Furthermore, the FOXC1 effect was not affected by SMO knockdown in SMO-expressing BLBC cells. 6 Consistent with our results, it has been shown that Hh signaling is highly active in breast CSCs that are characterized by the cell-surface glycoprotein CD44 C /CD24 ¡ phenotype. 9 Because FOXC1 stimulates Hh signaling independently of SMO, we postulated that elevated expression of FOXC1 may render cancer cells refractory to SMO targeting inhibitors.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…These cellular effects are dependent on downstream effectors such as MMP7 (matrix metalloproteinase 7) and SNAI1 (Snail family zinc finger 1), or activation of Hedgehog signaling. [7][8][9] Given the expression pattern and essential functional roles of FOXC1 in mesenchymal tissues, and the absence of any functional role for the gene in normal hematopoiesis, 2,5 we were surprised to discover though bioinformatics analyses that FOXC1 was among the most highly upregulated transcription factor genes in primary human acute myeloid leukemia (AML) stem and progenitor cells when compared with normal hematopoietic stem and progenitor cells (HSPCs). Indeed, in an extended analysis of 461 cases of human AML, FOXC1 was expressed at high level in approximately 20% of patient samples, 10 almost invariably in association with concomitant highlevel HOXA/B (Homeobox gene clusters A and B) expression (Fig.…”
mentioning
confidence: 99%